Positive electrode and nonaqueous electrolyte secondary battery

By using the mixing ratio of positive electrode active material particles with solid and hollow structures in the nonaqueous electrolyte secondary battery, the problem of difficult to take into account the output characteristics and storage characteristics in the positive electrode active material particles is solved, and the performance improvement of the non-aqueous electrolyte secondary battery is achieved. .

CN119314991APending Publication Date: 2025-01-14PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410926835.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-14
Filing Date
2024-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Although the hollow structure in the existing cathode active material particles improves the output characteristics, it is easy to react with the electrolyte to generate gas, affecting the storage characteristics, and it is difficult to take into account both excellent output characteristics and storage characteristics.

Method used

By adjusting the size and specific surface area of ​​the particles, a nonaqueous electrolyte secondary battery that takes into account both the output characteristics and the storage characteristics are achieved by adjusting the size and specific surface area of ​​the particles.

Benefits of technology

By adjusting the mixing ratio between the first positive electrode active material particles and the second positive electrode active material particles, the output characteristics and storage characteristics of the nonaqueous electrolyte secondary battery are taken into account, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314991A_ABST
    Figure CN119314991A_ABST
Patent Text Reader

Abstract

Provided is a technique capable of achieving a non-aqueous electrolyte secondary battery having both excellent output characteristics and storage characteristics. A positive electrode disclosed herein is provided with a positive electrode current collector (52) and a positive electrode active material layer (54) disposed on the surface of the positive electrode current collector (52). The positive electrode active material layer (54) contains first positive electrode active material particles (100) and second positive electrode active material particles (200). The first positive electrode active material particles (100) are solid particles having an average particle diameter of 1 [mu] m to 7 [mu] m as determined by a laser diffraction scattering method. The second positive electrode active material particles (200) are hollow particles having an average particle diameter of 8 [mu] m to 14 [mu] m as determined by a laser diffraction scattering method, the second positive electrode active material particles (200) being provided with an outer shell part (210) and a hollow part (220) surrounded by the outer shell part (210). The mass M1 of the first positive electrode active material particles (100) and the mass M2 of the second positive electrode active material particles (200) satisfy the formula 0 < M1 / (M1 + M2) < = 0.6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode and a non-aqueous electrolyte secondary battery. Background Art

[0002] As positive electrode active materials used in non-aqueous electrolyte secondary batteries, positive electrode active material particles having a hollow structure are known. Since the positive electrode active material particles have a hollow structure, the specific surface area is increased, so it is expected to improve output characteristics, for example. Patent documents 1 and 2 disclose positive electrode active materials having a hollow structure. Patent documents 3 and 4 disclose positive electrodes comprising positive electrode active material particles having a hollow structure and positive electrode active material particles having a solid structure.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2019-077577

[0006] Patent Document 2: International Publication No. 2014-181891

[0007] Patent Document 3: Japanese Patent Application Publication No. 2017-123236

[0008] Patent Document 4: Japanese Patent Application Publication No. 2021-120937 Summary of the invention

[0009] However, the output characteristics are improved by making the positive electrode active material particles into a hollow structure, but on the other hand, the following contradiction may occur: the specific surface area of ​​the positive electrode active material particles increases, the electrolyte and the positive electrode active material particles react easily, and gas is easily generated in the shell. Therefore, it is desired to have a technology that takes into account both output characteristics and storage characteristics.

[0010] Therefore, the main object of the present disclosure is to provide a technology capable of realizing a non-aqueous electrolyte secondary battery having both excellent output characteristics and storage characteristics.

[0011] One form of the technology disclosed herein is a positive electrode used in a non-aqueous electrolyte secondary battery. The positive electrode comprises a current collector and an active material layer disposed on the surface of the current collector. The active material layer comprises a first positive electrode active material particle and a second positive electrode active material particle. The average particle size of the first positive electrode active material particle based on the laser diffraction scattering method is 1 μm to 7 μm, and the porosity measured based on the cross-sectional SEM image is less than 10%. The second positive electrode active material particle comprises an outer shell and a hollow portion surrounded by the outer shell, the average particle size based on the laser diffraction scattering method is 8 μm to 14 μm, the proportion of voids measured based on the cross-sectional SEM image is more than 10%, and more than 80% of the voids exist on the inner side of the outer shell. The mass M1 of the first positive electrode active material particle and the mass M2 of the second positive electrode active material particle satisfy the following formula:

[0012] 0<M1 / (M1+M2)≤0.6.

[0013] The positive electrode has solid particles with fewer voids, namely the first positive electrode active material particles, and hollow particles with more voids, namely the second positive electrode active material particles. Since the size of the first positive electrode active material particles having a solid structure is smaller than the second positive electrode active material particles and is a smaller particle size (for example, less than 7 μm), the lithium diffusion distance in the first positive electrode active material particles is shortened, thereby improving the output characteristics of the secondary battery. In addition, since the size of the second positive electrode active material particles having a hollow structure is larger than the first positive electrode active material particles and is a larger particle size (for example, more than 8 μm), the specific surface area of ​​the second positive electrode active material particles is reduced, gas generation can be suppressed, and thus the storage characteristics are improved. By adjusting the mixing ratio of such first positive electrode active material particles and second positive electrode active material particles to an appropriate range, a non-aqueous electrolyte secondary battery that takes into account both excellent output characteristics and storage characteristics can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a cross-sectional view schematically showing a positive electrode sheet according to one embodiment.

[0015] Figure 2 This is a cross-sectional view schematically showing the structure of a second positive electrode active material particle according to one embodiment.

[0016] Figure 3 It is a cross-sectional view schematically showing the structure of a lithium ion secondary battery according to one embodiment.

[0017] Figure 4 It is a schematic exploded view showing the structure of a wound electrode body.

[0018] Figure 5 It is a schematic diagram showing a rough structure of a crystallization apparatus.

[0019] Explanation of symbols

[0020] 1Lithium-ion secondary battery

[0021] 20 wound electrode body

[0022] 30 battery housing

[0023] 36 Safety valve

[0024] 42 Positive terminal

[0025] 42a positive electrode collector plate

[0026] 44 Negative terminal

[0027] 44a Negative collector plate

[0028] 50 positive electrode sheet

[0029] 52 positive electrode collector

[0030] 52a Positive electrode current collector exposed portion

[0031] 54 Positive electrode active material layer

[0032] 60 negative electrode sheet

[0033] 62 negative electrode collector

[0034] 62a Negative electrode current collector exposed portion

[0035] 64 Negative electrode active material layer

[0036] 70 Isolation Parts

[0037] 100 first positive electrode active material particles

[0038] 200 Second positive electrode active material particles

[0039] 210 Shell

[0040] 212 primary particles

[0041] 220 Hollow

[0042] 300 crystallization device

[0043] 310 outer cylinder

[0044] 320 inner tube

[0045] 330 reaction chamber DETAILED DESCRIPTION

[0046] Hereinafter, the embodiments of the technology disclosed herein will be described with reference to the accompanying drawings. It should be noted that matters other than those specifically mentioned in this specification and matters required for the implementation of this technology (for example, the general structure and manufacturing process of the non-aqueous electrolyte secondary battery that does not characterize this technology, etc.) can be grasped as design matters for those skilled in the art based on the prior art in this field. This technology can be implemented based on the contents disclosed in this specification and the technical common sense in this field. It should be noted that each of the drawings is drawn schematically, and the dimensional relationships (length, width, thickness, etc.) do not necessarily reflect the actual dimensional relationships. In addition, in the following description of the drawings, the same symbols are marked for components and parts that play the same role, and repeated descriptions are sometimes omitted or simplified.

[0047] In this specification, when a numerical range is described as "A to B (here, A and B are arbitrary numerical values)", it includes the meaning of "greater than A and less than B", as well as the meaning of "greater than A and less than B", "greater than A and less than B", and "greater than A and less than B".

[0048] In this specification, "non-aqueous electrolyte secondary battery" refers to a storage device that uses a non-aqueous electrolyte as a charge carrier and can be repeatedly charged and discharged by accompanying the movement of charge carriers between positive and negative electrodes. In addition, in this specification, "lithium ion secondary battery" refers to a storage device that uses lithium ions as charge carriers and achieves charge and discharge by accompanying the movement of lithium ions between positive and negative electrodes.

[0049] The positive electrode disclosed herein is used for a non-aqueous electrolyte secondary battery, and is suitable for a lithium ion secondary battery. Figure 1 One embodiment of the positive electrode disclosed herein will be described in detail. Figure 1 2 is a cross-sectional view schematically showing a positive electrode sheet 50 of the present embodiment, and is a cross-sectional view along the thickness direction and the width direction. The positive electrode sheet 50 can be used as a positive electrode of a lithium ion secondary battery.

[0050] like Figure 1 As shown in FIG. 1 , the positive electrode sheet 50 includes a positive electrode current collector 52 and a positive electrode active material layer 54 disposed on the surface of the positive electrode current collector 52. Here, the positive electrode active material layer 54 is directly disposed on the surface of the positive electrode current collector 52, but it may also be disposed indirectly. The positive electrode active material layer 54 may be disposed only on one side of the positive electrode current collector 52, or may be disposed on a plurality of surfaces of the positive electrode current collector 52. Figure 1 As shown, they are arranged on both sides of the positive electrode collector 52.

[0051] like Figure 1As shown, at the end of the width direction of the positive electrode sheet 50, the positive electrode collector 52 may be provided with a positive electrode collector exposed portion 52a without a positive electrode active material layer 54. The positive electrode collector exposed portion 52a may function as a collector. In some embodiments, the positive electrode collector exposed portion 52a may be provided at the end of the positive electrode collector 52 processed into a tab shape.

[0052] The shape of the positive electrode collector 52 is foil-shaped (or sheet-shaped) in this embodiment, but is not limited thereto. The positive electrode collector 52 can be in various forms such as rod-shaped, plate-shaped, mesh-shaped, etc. As the properties of the positive electrode collector 52, as in the conventional lithium-ion secondary battery, a metal with good conductivity (such as aluminum, nickel, titanium, stainless steel, etc.) can be used, among which aluminum is preferred. As the positive electrode collector 52, aluminum foil is preferred.

[0053] The size of the positive electrode current collector 52 is not particularly limited and can be appropriately determined according to the battery design. When an aluminum foil is used as the positive electrode current collector 52 , the thickness thereof is not particularly limited, and is, for example, 5 μm to 35 μm, and preferably 6 μm to 20 μm.

[0054] The positive electrode active material layer 54 includes first positive electrode active material particles 100 and second positive electrode active material particles 200 .

[0055] The first positive electrode active material particle 100 is a solid particle having a solid structure. In this specification, a "solid particle" refers to a particle in which the ratio of voids (void ratio) to the entire cross section of the particle in a cross-sectional SEM image of the particle is less than 10%.

[0056] The porosity of the first positive electrode active material particle 100 measured by a cross-sectional SEM image is less than 10%, preferably less than 7%, and more preferably less than 5%. Thus, the capacity characteristics can be improved. It should be noted that in this specification, "porosity" refers to the arithmetic mean of the porosity of at least 100 randomly selected particles.

[0057] The shape of the first positive electrode active material particle 100 is not particularly limited, and may be, for example, spherical or substantially spherical. In some embodiments, the first positive electrode active material particle 100 may be amorphous.

[0058] In this specification, "roughly spherical" means a shape that can be roughly regarded as a sphere as a whole, and the average aspect ratio of the cross-sectional observation image based on an electron microscope is roughly 1 to 2, preferably 1 to 1.5, and more preferably 1 to 1.2. In addition, in this specification, "aspect ratio" refers to the value obtained by dividing the long side of the rectangle with the smallest area among the rectangles circumscribed with the outline of the particle by the short side. In addition, "average aspect ratio" refers to the arithmetic mean of the aspect ratios of at least 100 randomly selected particles.

[0059] The average particle size of the first positive electrode active material particles 100 is, for example, 1 μm or more, preferably 2 μm or more, and more preferably 3 μm or more. In addition, the average particle size of the first positive electrode active material particles 100 is, for example, 7 μm or less, preferably 6 μm or less, and more preferably 5 μm or less. The smaller the average particle size of the first positive electrode active material particles 100 of the solid particles, the shorter the lithium diffusion distance, so the output characteristics of the secondary battery can be improved.

[0060] In this specification, the “average particle size” refers to a particle size (D50) corresponding to 50% cumulative particle size distribution on a volume basis measured by a laser diffraction scattering particle size analyzer.

[0061] The BET specific surface area of ​​the first positive electrode active material particles 100 is, for example, 0.5 m 2 / g or above, 0.8m 2 / g or more, 1.5m 2 / g or above or 1.8m 2 / g or more. In addition, the BET specific surface area of ​​the first positive electrode active material particles 100 is, for example, 3 m 2 / g or less, 2.5m 2 / g or less, 2.4m 2 / g or less, 2.3m 2 / g or less or 2.2m 2 / g or less. The higher the BET specific surface area, the higher the output characteristics tend to be, and the lower the BET specific surface area, the higher the storage characteristics tend to be. By having the first positive electrode active material particle 100 have a BET specific surface area within the range specified by the upper and lower limits, the balance between the output characteristics and the storage characteristics can be appropriately adjusted, and the output characteristics and the storage characteristics can be achieved at a higher level.

[0062] The first positive electrode active material particles 100 may be, for example, lithium transition metal composite oxides, lithium transition metal phosphate compounds, etc. The crystal structure of the positive electrode active material is not particularly limited, and may be a layered structure, a spinel structure, an olivine structure, or the like.

[0063] As a lithium transition metal composite oxide, it is preferred to contain at least one of Ni, Co, and Mn as a transition metal element. Specific examples thereof include lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium iron nickel manganese composite oxides.

[0064] It should be noted that in this specification, "lithium nickel cobalt manganese composite oxide" refers to a term that refers to an oxide containing one or more additional elements other than Li, Ni, Co, Mn, and O in addition to oxides containing these elements. Examples of the additional elements include transition metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn, typical metal elements, and the like. In addition, the additional elements may also be metalloid elements such as B, C, Si, and P, and non-metallic elements such as S, F, Cl, Br, and I. This is also the same for the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.

[0065] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO 4 ), lithium manganese phosphate (LiMnPO 4 ), and lithium manganese iron phosphate.

[0066] In this embodiment, the first positive electrode active material particles 100 have a composition represented by the following general formula (i):

[0067] Li d Ni (1-x-y-z) Co x Mn y A z O2(i)

[0068] In general formula (i), 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.1, and 0.95≤d≤1.2 are satisfied. In general formula (i), A is one or more elements selected from Al, Ti, Zr, Nb, Mo, and W.

[0069] In some embodiments, the first positive electrode active material particles 100 contain at least Ni as a transition metal. That is, in this embodiment, the general formula (i) further satisfies x+y+z<1.

[0070] In some embodiments, the ratio of Ni is higher than the total ratio of Co and Mn. That is, in the general formula (i), x+y+z<0.5 may be satisfied.

[0071] In some embodiments, the first positive electrode active material particles 100 include Ni, Co, and Mn. That is, in general formula (i), 0<x<0.5 and 0<y<0.5 may be satisfied. In some embodiments, 0<x<0.3 and 0<y<0.3 may be satisfied.

[0072] The second positive electrode active material particles 200 are hollow particles having a hollow structure. Figure 22 is a cross-sectional view schematically showing the structure of the second positive electrode active material particle 200 of this embodiment. The second positive electrode active material particle 200 includes an outer shell portion 210 and a hollow portion 220 .

[0073] In this specification, "hollow particles" refer to particles in which the ratio of voids in a cross-sectional SEM image of the particle is 10% or more relative to the entire particle cross section, and 70% or more of the voids are located inside the particle rather than the outer shell.

[0074] The porosity of the second positive electrode active material particles 200 measured by cross-sectional SEM images is, for example, 10% or more, preferably 20% or more, and more preferably 25% or more. This increases the specific surface area, makes it easier for Li ions to react, and improves output characteristics.

[0075] The shape of the second positive electrode active material particles 200 is not particularly limited, and may be, for example, spherical or substantially spherical. In some embodiments, the second positive electrode active material particles 200 may be amorphous.

[0076] The average particle size of the second positive electrode active material particles 200 is, for example, 8 μm or more, 9 μm or more, 10 μm or more, or 11 μm or more. In addition, the average particle size of the second positive electrode active material particles 200 is, for example, 14 μm or less, preferably 13 μm or less, and more preferably 12 μm or less. The larger the average particle size of the second positive electrode active material particles 200 of the hollow particles, the more the reactivity of the second positive electrode active material particles 200 with the electrolyte can be suppressed, so there is a tendency to suppress gas generation and improve the storage characteristics of the secondary battery. In addition, the smaller the average particle size of the second positive electrode active material particles 200, the greater the specific surface area, so there is a tendency to improve the output characteristics. By having the second positive electrode active material particles 200 have an average particle size in the range specified by the above upper and lower limits, the balance between the output characteristics and the storage characteristics can be appropriately adjusted.

[0077] The shell 210 includes a plurality of primary particles 212. In the present embodiment, the shell 210 is formed by aggregating a plurality of primary particles 212 through physical or chemical bonding forces. In the present specification, "primary particle" refers to the smallest unit constituting a positive electrode active material particle, specifically, the smallest unit determined by the geometrical appearance.

[0078] The outer shell 210 may be a single-layer structure or a multi-layer structure in which a plurality of layers are stacked.

[0079] The average thickness of the outer shell 210 can be, for example, less than 1 / 5, preferably less than 1 / 6, relative to the average particle size of the second positive electrode active material particles 200. In addition, the average thickness of the outer shell 210 can be, for example, more than 1 / 10 or more than 1 / 8 relative to the average particle size of the second positive electrode active material particles 200. By thinning the average thickness of the outer shell 210 relative to the average particle size of the second positive electrode active material particles 200, the diffusion resistance of Li ions is reduced, and the output characteristics are improved.

[0080] It should be noted that in this specification, the thickness of the outer shell 210 refers to the thickness measured in the cross-sectional observation image of the second positive electrode active material particle 200 based on an electron microscope, and the average thickness of the outer shell 210 refers to the arithmetic mean of the thickness of the outer shell 210 measured in at least 100 second positive electrode active material particles 200.

[0081] The shape of the primary particle 212 may be, for example, needle-shaped, plate-shaped, elliptical, etc. In addition, the average aspect ratio (length of the major axis / length of the minor axis) of the cross-sectional observation image of the second positive electrode active material particle 200 based on an electron microscope is, for example, 2 or more, preferably 3 or more, and more preferably 5 or more. The longer the average aspect ratio of the primary particle 212, the lower the diffusion resistance of Li ions. The average aspect ratio of the primary particle 212 may be, for example, 50 or less, 20 or less, or 10 or less.

[0082] The average length of the major axis of the primary particles 212 is, for example, 0.05 μm or more, 0.1 μm or more, 0.2 μm or more, or 0.3 μm or more. The average length of the major axis of the primary particles 212 is, for example, 1.2 μm or less, 1 μm or less, or 0.8 μm or less.

[0083] The average length of the minor axis of the primary particles 212 is, for example, 0.01 μm or more, 0.02 μm or more, 0.05 μm or more, or 0.1 μm or more, or 0.6 μm or less, 0.4 μm or less, or 0.2 μm or less.

[0084] The average lengths of the major and minor axes of the primary particles 212 are measured based on an electron microscope cross-sectional observation image of the second positive electrode active material particle 200. In this specification, the average lengths of the major and minor axes of the primary particles 212 refer to the arithmetic mean of the major and minor axes of at least 100 primary particles 212.

[0085] More than 40% of the primary particles 212 contained in the shell portion 210 are radially oriented from the center of the second positive electrode active material particle 200 to the surface of the second positive electrode active material particle 200. In a preferred embodiment, the oriented primary particles 212 are more than 45%, more than 55%, more than 65% or more than 70%. By having more primary particles 212 radially oriented, the softness of the second positive electrode active material particle 200 is improved and it is not easy to be damaged. It should be noted that the ratio of the primary particles 212 is expressed based on the number, which represents the ratio of the number of radially oriented primary particles 212 in the total number of primary particles 212 measured (at least 100).

[0086] In this specification, "primary particles are radially oriented" means that the angle formed by the long axis direction of the primary particle 212 relative to the reference line connecting the center of the primary particle 212 and the center of the second positive electrode active material particle 200 is 30° or less. It should be noted that the measurement can be performed by processing the cross section of the second positive electrode active material particle 200 using an ion beam and observing the cross section using an electron microscope. It should be noted that as another method, the orientation can also be confirmed by electron beam backscatter diffraction (EBSD).

[0087] The hollow portion 220 is a space surrounded by the outer shell 210. The hollow portion 220 may not be completely surrounded by the outer shell 210, and may include a form in which a portion of the outer shell 210 is missing. In a preferred embodiment, in the hollow portion 220, the number of primary particles is less than that of the outer shell 210 or there are no primary particles. That is, the ratio of the primary particles 212 contained in the outer shell 210 in the primary particles contained in the second positive electrode active material particles 200 as a whole may be, for example, 90% or more, 95% or more, 98% or more, or 100%. Thus, an active material that reacts well with Li during firing can be obtained.

[0088] In addition, in this specification, the ratio of the primary particles is measured by the area ratio of the cross-sectional SEM.

[0089] The composition of the second positive electrode active material particles 200 may be the same as that of the first positive electrode active material particles 100. The first positive electrode active material particles 100 and the second positive electrode active material particles 200 may have the same composition or different compositions. In a preferred embodiment, the second positive electrode active material particles 200 are lithium transition metal composite oxides containing at least lithium and nickel.

[0090] In the present embodiment, the second positive electrode active material particles 200 are lithium transition metal composite oxides containing lithium and transition metals, and have a composition represented by the above general formula (i).

[0091] In some embodiments, the second positive electrode active material particles 200 include Ni, Co, and Mn. That is, in general formula (i), 0<x<0.5 and 0<y<0.5 may be satisfied. In some embodiments, 0<x<0.3 and 0<y<0.3 may be satisfied.

[0092] exist Figure 2 In the embodiment shown, the second positive electrode active material particle 200 has an outer shell 210 and a hollow portion 220, but in other embodiments, it may further have a central portion formed by the aggregation of primary particles. The central portion exists inside the outer shell. A space where no primary particles exist may be provided between the central portion and the outer shell. In addition, the central portion may be a solid structure or a hollow structure.

[0093] When the mass of the first positive electrode active material particles 100 is set to M1 and the mass of the second positive electrode active material particles 200 is set to M2, the ratio of the first positive electrode active material particles 100 and the second positive electrode active material particles 200 contained in the positive electrode active material layer 54 satisfies the formula: 0<M1 / (M1+M2)≤0.6. In addition, M1 / (M1+M2) is preferably greater than 0.05, and more preferably greater than 0.1. In addition, M1 / (M1+M2) is preferably less than 0.3, and more preferably less than 0.2. As a result, the balance of the first positive electrode active material particles 100 of the solid particles and the second positive electrode active material particles 200 of the hollow particles becomes appropriate, and both the output characteristics and the storage characteristics are well exerted.

[0094] The total ratio of the first positive electrode active material particles 100 and the second positive electrode active material particles 200 contained in the positive electrode active material layer 54 is preferably 80 wt% or more, more preferably 85 wt% or more, and further preferably 95 wt% or more of the entire positive electrode active material layer 54. In addition, although not particularly limited, the total ratio of the first positive electrode active material particles 100 and the second positive electrode active material particles 200 contained in the positive electrode active material layer 54 may be 99 wt% or less of the entire positive electrode active material layer 54.

[0095] The positive electrode active material layer 54 may further include a conductive material, a binder, and the like. As a conductive material, for example, carbon black such as acetylene black (AB), and other carbon materials (carbon nanotubes, graphite, etc.) can be used well. As a binder, for example, polyvinylidene fluoride (PVDF) and the like can be used. There is no particular limitation, but the proportion of the conductive material is, for example, less than 5wt% of the entire positive electrode active material layer 54, preferably less than 3wt%, and more preferably less than 1wt%. In addition, there is no particular limitation, but the proportion of the binder is, for example, less than 5wt% of the entire positive electrode active material layer 54, preferably less than 3wt%, and more preferably less than 1wt%.

[0096] The positive electrode sheet 50 can be produced by a known method. Specifically, for example, a slurry containing the constituent components of the positive electrode active material layer 54 is prepared. The slurry is applied to the positive electrode collector 52 and dried to form the positive electrode active material layer 54 on the positive electrode collector 52. It should be noted that the positive electrode active material layer 54 can be subjected to a pressing process as needed.

[0097] The first positive electrode active material particles and the second positive electrode active material particles used in the present technology may be purchased from the market, or may be processed by a known method, or may be manufactured. An example of a method for manufacturing the second positive electrode active material particles 200 is described in the test examples described below.

[0098] For the positive electrode sheet 50 of the present embodiment, the size of the first positive electrode active material particle 100 having a solid structure is smaller than the second positive electrode active material particle 200, and is a smaller particle size (for example, less than 7 μm). As a result, the lithium diffusion distance in the first positive electrode active material particle 100 is shortened, and therefore, the output characteristics of the secondary battery can be improved. In addition, the size of the second positive electrode active material particle 200 having a hollow structure is larger than the first positive electrode active material particle 100, and is a larger particle size (for example, more than 8 μm). As a result, the specific surface area of ​​the second positive electrode active material particle 200 is reduced, gas generation is suppressed, and thus the storage characteristics are improved. By adjusting the mixing ratio of such a first positive electrode active material particle 100 and the second positive electrode active material particle 200 to an appropriate range (for example, more than 0 and less than 0.6), a non-aqueous electrolyte secondary battery that takes into account both excellent output characteristics and storage characteristics can be achieved.

[0099] Hereinafter, a nonaqueous electrolyte secondary battery including the positive electrode sheet 50 will be described by taking a lithium ion secondary battery as an example. Figure 3 It is a cross-sectional view schematically showing the structure of a lithium ion secondary battery 1 according to one embodiment. Figure 3 The lithium-ion secondary battery 1 is a sealed battery in which a flat wound electrode body 20 and a non-aqueous electrolyte (not shown) are housed in a flat square battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive terminal 42 and a negative terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or more. The positive and negative terminals 42 and 44 are electrically connected to the positive and negative collector plates 42a and 44a, respectively. The material of the battery case 30 is a metal material that is lightweight and has good thermal conductivity, such as aluminum.

[0100] Figure 4 2 is a schematic exploded view showing the structure of the wound electrode body 20. Figure 3 and Figure 4As shown, the wound electrode body 20 has a form in which the positive electrode sheet 50 and the negative electrode sheet 60 are overlapped and wound in the length direction with two long strip separators 70 interposed therebetween. The positive electrode sheet 50 has a structure in which a positive electrode active material layer 54 is formed on one side or both sides (here both sides) of a long strip positive electrode collector 52 along the length direction. The negative electrode sheet 60 has a structure in which a negative electrode active material layer 64 is formed on one side or both sides (here both sides) of a long strip negative electrode collector 62 along the length direction. The positive electrode collector exposed portion 52a and the negative electrode collector exposed portion 62a (i.e., the portion where the negative electrode collector 62 is exposed without forming the negative electrode active material layer 64) are formed to extend outward from both ends of the winding axis direction (i.e., the sheet width direction orthogonal to the above-mentioned length direction) of the wound electrode body 20. The positive electrode current collector plate 42a and the negative electrode current collector plate 44a are joined to the positive electrode current collector exposed portion 52a and the negative electrode current collector exposed portion 62a, respectively.

[0101] As the negative electrode collector 62 constituting the negative electrode sheet 60, a known negative electrode collector used in a lithium ion secondary battery can be used, for example, a sheet or foil made of a metal with good conductivity (such as copper, nickel, titanium, stainless steel, etc.). As the negative electrode collector 62, copper foil is preferred. The size of the negative electrode collector 62 is not particularly limited and can be appropriately determined according to the battery design. When copper foil is used as the negative electrode collector 62, its thickness is not particularly limited, for example, 5μm to 35μm, preferably 7μm to 20μm.

[0102] The negative electrode active material layer 64 includes a negative electrode active material. As the negative electrode active material, for example, carbon materials such as graphite, hard carbon, and soft carbon can be used. The negative electrode active material layer 64 may further include a binder, a thickener, and the like. As the binder, for example, styrene butadiene rubber (SBR) and the like can be used. As the thickener, for example, carboxymethyl cellulose (CMC) and the like can be used.

[0103] As the separator 70, various porous sheets similar to those used in lithium-ion secondary batteries can be used, and examples thereof include porous resin sheets made of resins such as polyethylene (PE) and polypropylene (PP). The porous resin sheet can be a single-layer structure or a multi-layer structure of two or more layers (for example, a three-layer structure in which PP layers are stacked on both sides of a PE layer). The separator 70 can also have a heat-resistant layer (HRL).

[0104] As a non-aqueous electrolyte, the same non-aqueous electrolyte as that of a conventional lithium-ion secondary battery can be used, and typically a non-aqueous electrolyte containing a supporting salt in an organic solvent (non-aqueous solvent) can be used. As a non-aqueous solvent, aprotic solvents such as carbonates, esters, and ethers can be used. Among them, carbonates are preferred because the effect of reducing the low-temperature resistance of the positive electrode material becomes particularly high. Examples of carbonates include ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC), etc. Such non-aqueous solvents can be used alone or in appropriate combinations of two or more. As a supporting salt, for example, lithium salts such as LiPF6, LiBF4, and lithium bis(fluorosulfonyl)imide (LiFSI) can be used well. The concentration of the supporting salt is preferably 0.7 mol / L to 1.3 mol / L.

[0105] The nonaqueous electrolyte may contain components other than the nonaqueous solvent and supporting salt, such as various additives such as a gas generating agent, a film forming agent, a dispersant, and a thickener, as long as the effects of the present invention are not significantly impaired.

[0106] As an embodiment, a square lithium-ion secondary battery having a flat wound electrode body is described above. However, the lithium-ion secondary battery can also be configured as a lithium-ion secondary battery having a stacked electrode body (i.e., an electrode body formed by alternating stacking of multiple positive electrodes and multiple negative electrodes). In addition, the lithium-ion secondary battery can also be configured as a cylindrical lithium-ion secondary battery, a laminated shell type lithium-ion secondary battery, etc. Furthermore, an all-solid secondary battery in which the electrolyte is a solid electrolyte can also be constructed.

[0107] The lithium-ion secondary battery 1 can be used for various purposes. Suitable uses include a driving power source mounted on a vehicle such as an electric vehicle (BEV), a hybrid electric vehicle (HEV), and a plug-in hybrid electric vehicle (PHEV). In addition, the lithium-ion secondary battery 1 can be used as a storage battery for a small power storage device, etc. The lithium-ion secondary battery 1 can also be used in the form of a battery pack in which a plurality of batteries are connected in series and / or in parallel.

[0108] As described above, specific aspects of the technology disclosed herein include the following items.

[0109] Item 1: A positive electrode used in a non-aqueous electrolyte secondary battery, comprising a current collector and an active material layer disposed on a surface of the current collector.

[0110] The active material layer includes first positive electrode active material particles and second positive electrode active material particles.

[0111] The first positive electrode active material particles have an average particle size of 1 μm to 7 μm based on a laser diffraction scattering method, and a porosity of less than 10% based on a cross-sectional SEM image measurement.

[0112] The second positive electrode active material particles include an outer shell and a hollow portion surrounded by the outer shell, an average particle size based on a laser diffraction scattering method of 8 μm to 14 μm, a ratio of voids measured based on a cross-sectional SEM image of 10% or more, and more than 80% of the voids are present inside the outer shell,

[0113] The mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles satisfy the following formula:

[0114] 0<M1 / (M1+M2)≤0.6.

[0115] Item 2: The positive electrode according to Item 1, wherein the BET specific surface area of ​​the first positive electrode active material particles is 1.5 m 2 / g~2.3m 2 / g.

[0116] Item 3: The positive electrode according to Item 1 or 2, wherein the mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles satisfy the following formula:

[0117] 0<M1 / (M1+M2)≤0.2.

[0118] Item 4: The positive electrode according to any one of Items 1 to 3, wherein 90% or more of the primary particles contained in the entire second positive electrode active material particles are present in the outer shell portion.

[0119] Item 5: A positive electrode according to any one of Items 1 to 4, wherein, for more than 40% of the primary particles present in the above-mentioned outer shell portion, the angle formed by the long axis direction of the above-mentioned primary particles relative to the baseline connecting the center of the primary particles and the center of the above-mentioned second positive electrode active material particles is less than 30°.

[0120] Item 6: The positive electrode according to any one of Items 1 to 5, wherein the first positive electrode active material particles and the second positive electrode active material particles are each a compound represented by the following general formula: Li d Ni (1-x-y-z) Cox Mn y A z O2

[0121] (wherein, 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.1, 0.95≤d≤1.2, and A is one or more additional elements selected from the group consisting of Al, Ti, Zr, Nb, Mo, and W).

[0122] Item 7: A nonaqueous electrolyte secondary battery comprising the positive electrode according to any one of Items 1 to 6.

[0123] Hereinafter, test examples related to the present technology will be described. However, the present technology is not limited to the contents shown in the following test examples.

[0124] [Preparation of Hollow Structured Positive Electrode Active Material Particles]

[0125] A crystallization apparatus capable of generating Taylor vortices in the reaction chamber 330 is used. Figure 5 The general structure of the crystallization device 300 used is shown in FIG. Figure 5 As shown, the crystallization device 300 includes a cylindrical outer cylinder 310, a cylindrical inner cylinder 320 coaxially arranged with the outer cylinder 310, and a motor 322 connected to the inner cylinder 320. The diameter of the inner cylinder 320 is smaller than that of the outer cylinder 310. The crystallization device 300 has a reaction chamber 330 between the outer cylinder 310 and the inner cylinder 320. The reaction chamber 330 is a region where the crystallization reaction is performed and is a region where Taylor vortices 332 and 334 are generated. It should be noted that the Taylor vortex represents the flow of a fluid that generates the Taylor vortex. The Taylor vortex represents the form of a vortex of annular flow.

[0126] As an example of the preparation of the positive electrode active material particles with a hollow structure, first, the oxygen concentration in the 0.1L reaction chamber 330 is set to 25 vol%, 1 wt% ammonia water is added, and the inner cylinder 320 is rotated at a speed of 2000 rpm with the axis of the inner cylinder 320 as the center to generate Taylor vortex in the ammonia water in the reaction chamber 330. Figure 5 Only parts of Taylor vortices 332 and 334 are shown, but Taylor vortices are generated throughout the entire reaction chamber 330. Next, a 30 wt % sodium hydroxide aqueous solution is supplied to the reaction chamber 330, and the mixed liquid in the reaction chamber 330 is adjusted to pH 12 based on a liquid temperature of 25°C.

[0127] Nickel sulfate, cobalt sulfate and manganese sulfate were dissolved in water to prepare a 1 mol / L raw metal aqueous solution. At this time, the molar ratio of nickel sulfate:cobalt sulfate:manganese sulfate was 60:20:20.

[0128] The raw metal aqueous solution, 1 wt% ammonia aqueous solution and 30 wt% sodium hydroxide aqueous solution were supplied from the first supply port 312, the second supply port 314 and the third supply port 316 in a ratio of 1:1:1 on a volume basis to the mixed solution in the reaction chamber 330, and crystallization was performed for 30 minutes under the condition of pH 12. Then, the crystallized product was taken out from the discharge port 318, washed with water, filtered and dried, thereby obtaining a powdery composite hydroxide (precursor).

[0129] The ICP emission spectrometer confirmed that the composite hydroxide obtained above was Ni 0.6 Co 0.2 Mn 0.2 (OH)2.

[0130] A lithium compound is mixed with the composite hydroxide in such a manner that the molar ratio (Li:M) of lithium (Li) to a metal element (M) other than lithium is 1.1:1. The mixture is fired in a firing furnace at 700°C in an oxidizing atmosphere for 5 hours. Thus, a positive electrode active material is obtained. The positive electrode active material thus obtained is used as a second active material in some of the following examples.

[0131] [Measurement of Average Particle Diameter of Positive Electrode Active Material Particles]

[0132] The average particle size of the positive electrode active material was evaluated as a particle size (D50) corresponding to 50% cumulative particle size distribution based on volume measured by a laser diffraction scattering particle size analyzer.

[0133] [Evaluation of the structure of the positive electrode active material]

[0134] In order to observe the cross-sectional shape of the positive electrode active material particles, the positive electrode active material particles are cross-sectionally processed using an ion beam to obtain an SEM image of the cross-sectional shape of the positive electrode active material particles. Based on the SEM image, the proportion of the void portion (the proportion of the void portion of the cross-sectional area of ​​the particle) and distribution are determined. A structure with a void ratio of less than 10% is rated as a solid structure. In addition, a structure with a void ratio of more than 10% and more than 80% of the voids located on the inner side of the outer shell is rated as a hollow structure.

[0135] It was confirmed that the positive electrode active material particles obtained by the method accompanied by the above-mentioned Taylor vortex flow have an outer shell and a hollow part surrounded by the outer shell, have a porosity of 25% or more, and that 90% or more of the primary particles constituting the particles in the cross section are present in the outer shell.

[0136] [Evaluation of Orientation Ratio of Hollow Structured Positive Electrode Active Material]

[0137] For the positive electrode active material particles with a hollow structure, the orientation of the primary particles contained in the shell portion was confirmed by SEM observation of the cross section of the particles. Specifically, the angle formed by the long axis direction of the primary particle relative to the reference line connecting the center of the primary particle and the center of the positive electrode active material particle is 30° or less. The primary particles contained in the shell portion of more than 100 were randomly observed to determine the proportion of primary particles oriented radially (radial orientation rate). The results are shown in Table 1.

[0138] In addition, cross-sectional SEM images were also taken of the precursor particles of the positive electrode active material particles, and it was confirmed that the aspect ratio and orientation ratio of the primary particles hardly changed before and after sintering.

[0139] [Measurement of BET specific surface area of ​​positive electrode active material]

[0140] The BET specific surface area of ​​the positive electrode active material was measured using a flow-type gas adsorption method specific surface area measuring device.

[0141] (Example 1)

[0142] [Production of positive electrode plate (positive electrode sheet)]

[0143] Prepare a particle size of 3 μm and a BET specific surface area of ​​2.2 m 2 / g solid structure of the first active material and the average particle size of the second active material obtained by the above method is 12μm and the radial orientation rate is 75%. The chemical formula of the first active material and the second active material is Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 Chemical formula represented by O2. The first active material and the second active material are mixed in a mass ratio of 20:80 to prepare the positive electrode active material of Example 1. The positive electrode active material obtained above: conductive material: binder = 100:1:1 (weight basis) is mixed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture paste. Acetylene black is used as the conductive material. PVDF is used as the binder. The prepared positive electrode mixture paste is applied on a 13μm aluminum foil and dried, then pressed to a specified thickness and processed into a specified size to produce a positive electrode plate.

[0144] [Manufacturing of negative electrode plate (negative electrode sheet)]

[0145] Graphite:SBR:CMC=100:1:1 (weight basis) was mixed with water to prepare a negative electrode mixture paste. The prepared negative electrode mixture paste was applied on a copper foil and dried, then pressed to a predetermined thickness and cut into a predetermined size to prepare a negative electrode plate.

[0146] [Fabrication of non-aqueous electrolyte secondary battery]

[0147] The prepared positive electrode plate and negative electrode plate are stacked on each other with a separator between them to prepare a stacked electrode body. Leads are respectively installed on the positive electrode plate and the negative electrode plate. After the prepared stacked electrode body is housed in an outer casing composed of an aluminum laminate sheet, a non-aqueous electrolyte is injected, and the opening of the outer casing is sealed to prepare a test single cell (laminated single cell). It should be noted that the non-aqueous electrolyte uses a solvent composed of EC:FEC:EMC:DMC=15:5:40:40 (volume basis) and a non-aqueous electrolyte containing 1M LiPF6 as a Li salt.

[0148] (Example 2)

[0149] Prepare a particle size of 5 μm and a BET specific surface area of ​​1.8 m 2 / g solid structure of the first active material and the average particle size of the second active material obtained by the above method is 9μm and the radial orientation rate is 68%. The chemical formula of the first active material and the second active material is Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 The chemical formula represented by O2 was obtained. The first active material and the second active material were mixed in a mass ratio of 10:90 to prepare the positive electrode active material of Example 2. The subsequent steps until the preparation of the test single cell were the same as those of Example 1.

[0150] (Example 3)

[0151] Prepare a particle size of 5 μm and a BET specific surface area of ​​1.8 m 2 / g of a solid structure of the first active material and an average particle size of 10μm of the second active material of the hollow structure. The second active material is composed of secondary particles formed by the aggregation of multiple primary particles. The secondary particles have a central portion of a hollow structure, a space portion outside the central portion where no primary particles exist, and an outer shell portion electrically connected to the central portion. The average value of the ratio of the outer diameter of the central portion of the secondary particle to the particle size of the secondary particle is 30 to 80%. In addition, the radial orientation rate of the primary particles constituting the outer shell of the secondary particle is 70%. The chemical formulas of the first active material and the second active material are both composed of Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 The chemical formula represented by O2 was obtained. The first active material and the second active material were mixed in a mass ratio of 10:90 to prepare the positive electrode active material of Example 3. The subsequent steps until the preparation of the test single cell were the same as those of Example 1.

[0152] (Example 4)

[0153] Prepare a particle size of 4 μm and a BET specific surface area of ​​0.8 m 2 / g solid structure of the first active material and the average particle size of the second active material obtained by the above method is 12μm and the radial orientation rate is 65%. The chemical formula of the first active material and the second active material is Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 The chemical formula represented by O2 was obtained. The first active material and the second active material were mixed in a mass ratio of 20:80 to prepare the positive electrode active material of Example 4. The subsequent steps until the preparation of the test single cell were the same as those of Example 1.

[0154] (Example 5)

[0155] Prepare a particle size of 4 μm and a BET specific surface area of ​​2.4 m 2 / g solid structure of the first active material and the average particle size of the second active material obtained by the above method is 12μm and the radial orientation rate is 65%. The chemical formula of the first active material and the second active material is Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 The chemical formula represented by O2 was obtained. The first active material and the second active material were mixed in a mass ratio of 60:40 to prepare the positive electrode active material of Example 5. The subsequent steps until the preparation of the test single cell were the same as those of Example 1.

[0156] (Comparative Example 1)

[0157] Prepare a particle size of 5 μm and a BET specific surface area of ​​2.4 m 2 / g of a solid structure of the first active material and an average particle size of 5μm of the second active material of the hollow structure. The second active material is composed of secondary particles formed by the aggregation of multiple primary particles. The secondary particles have a central part of a hollow structure, a space part outside the central part where no primary particles exist, and an outer shell part electrically connected to the central part. The average value of the ratio of the outer diameter of the central part of the secondary particle to the particle size of the secondary particle is 30 to 80%. In addition, the radial orientation rate of the primary particles constituting the outer shell of the secondary particle is 65%. The chemical formulas of the first active material and the second active material are both composed of Li 1.1 Ni 0.6 Co 0.2 Mn 0.2The chemical formula represented by O2 was obtained. The first active material and the second active material were mixed in a mass ratio of 20:80 to prepare the positive electrode active material of Comparative Example 1. The subsequent steps until the preparation of the test single cell were the same as those of Example 1.

[0158] (Comparative Example 2)

[0159] Prepare a particle size of 10 μm and a BET specific surface area of ​​3.4 m 2 / g solid structure of the first active material and the average particle size of the second active material obtained by the above method is 12μm and the radial orientation rate is 55%. The chemical formula of the first active material and the second active material is Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 The chemical formula represented by O2 was obtained. The first active material and the second active material were mixed in a mass ratio of 30:70 to prepare the positive electrode active material of Comparative Example 2. The subsequent steps until the preparation of the test single cell were the same as those of Example 1.

[0160] <Determination of initial capacity>

[0161] Under 25°C environment, the test single cell was CCCV charged to 4.2V. The current value of CC charging at this time was C / 3. Then, it was discharged to 3V at the current value of C / 3. The discharge capacity at this time was taken as the initial capacity. Table 1 shows the results based on Comparative Example 1.

[0162] <IV resistance measurement>

[0163] At 25°C, charge the test battery to 50% SOC (state of charge) and leave it for 1 hour. Then, discharge it at 5C for 10 seconds. When the OCV voltage just before discharge is set as V0 and the voltage at the time of 10 seconds of discharge is set as V1, the IV resistance value is calculated using the following formula:

[0164] Formula: IV resistance = (V0-V1) / 5C current value

[0165] Table 1 shows the results as ratios based on Comparative Example 1 described later.

[0166] <Measurement of gas generation amount>

[0167] Under 25°C environment, the test single cell is charged with CCCV at a charging potential of 4.4V and a charging current of 0.3C. Charging is completed when the charging current reaches 0.01C. After charging, the test single cell is placed in a constant temperature bath at 60°C and stored for 24 hours. Then, the test single cell is cooled in an atmosphere of 25°C. After cooling, the volume change of the test single cell before and after storage is measured, and the amount of gas generated during storage (mL) is calculated. The volume of the test single cell before and after storage is measured using the Archimedean principle, and the difference is taken as the amount of gas generated.

[0168] [Table 1]

[0169]

[0170] <Evaluation of test examples>

[0171] Comparative Example 1 is a test example of a secondary battery with excellent output characteristics and low resistance achieved by using smaller hollow particles with an average particle size of 5 μm, but the amount of gas generated is large and there is room for improvement in the storage characteristics. Here, when comparing Examples 1 to 5 with Comparative Example 1, as shown in Table 1, Examples 1 to 5 can reduce the amount of gas generated while maintaining the same resistance or further suppressing the resistance compared to Comparative Example 1. That is, it can be seen that in Examples 1 to 5, the storage characteristics are improved, and a secondary battery with both excellent output characteristics and storage characteristics is achieved.

[0172] The specific examples of the present technology have been described in detail above, but these are merely examples and do not limit the scope of the claims. The technology described in the scope of the claims includes various modifications and changes to the specific examples described above.

Claims

1. A positive electrode used in a non-aqueous electrolyte secondary battery, comprising a current collector and an active material layer disposed on a surface of the current collector, The active material layer includes first positive electrode active material particles and second positive electrode active material particles. The first positive electrode active material particles have an average particle size of 1 μm to 7 μm based on a laser diffraction scattering method, and a porosity of less than 10% based on a cross-sectional SEM image measurement. The second positive electrode active material particles have an outer shell and a hollow portion surrounded by the outer shell, an average particle size based on a laser diffraction scattering method is 8 μm to 14 μm, a proportion of voids measured based on a cross-sectional SEM image is 10% or more, and 80% or more of the voids are present inside the outer shell, The mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles satisfy the following formula: 0<M1 / (M1+M2)≤0.

6.

2. The positive electrode according to claim 1, wherein The BET specific surface area of ​​the first positive electrode active material particles is 1.5 m 2 / g~2.3m 2 / g.

3. The positive electrode according to claim 1, wherein The mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles satisfy the following formula: 0<M1 / (M1+M2)≤0.

2.

4. The positive electrode according to claim 1, wherein 90% or more of the primary particles contained in the entire second positive electrode active material particles are present in the outer shell portion.

5. The positive electrode according to claim 4, wherein For 40% or more of the primary particles present in the outer shell, the angle formed by the major axis direction of the primary particle with respect to a reference line connecting the center of the primary particle and the center of the second positive electrode active material particle is 30° or less.

6. The positive electrode according to claim 1, wherein The first positive electrode active material particles and the second positive electrode active material particles are each a compound represented by the following general formula, Li d Ni (1-x-y-z) Co x Mr y A z O2 Among them, 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.1, 0.95≤d≤1.2, and A is one or more additional elements selected from Al, Ti, Zr, Nb, Mo, and W. 7 . A non-aqueous electrolyte secondary battery comprising the positive electrode according to claim 1 .

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2017123236A

  • Transition metal composite hydroxide particles, production method thereof, positive electrode active material for lithium ion secondary battery, production method thereof, and lithium ion secondary battery

    JP2019077577A

  • Positive electrode active material for lithium ion secondary battery, positive electrode and lithium ion secondary battery

    JP2021120937A

  • Transition metal composite hydroxide particles, method for producing same, positive electrode active material for non-aqueous electrolyte secondary battery, method for producing same, and non-aqueous electrolyte secondary battery

    WO2014181891A1